2019
DOI: 10.3389/fpls.2019.00872
|View full text |Cite
|
Sign up to set email alerts
|

ABA Alleviates Uptake and Accumulation of Zinc in Grapevine (Vitis vinifera L.) by Inducing Expression of ZIP and Detoxification-Related Genes

Abstract: Abscisic acid (ABA) is a plant hormone that can mitigate heavy metal toxicity. Exogenous ABA and ABA mimic 1 (AM1) were applied to study the influence on Zn uptake and accumulation in Vitis vinifera L. cv. Merlot seedlings exposed to excess Zn. The seedlings were treated with either normal or excess levels of Zn in combination with applications of ABA and AM1. Excess Zn exposure resulted in decreased lateral root length, decreased photosynthesis, elevated uptake, and accumulation of Zn i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 60 publications
2
28
2
Order By: Relevance
“…However, blades collected in the 2018-19 season presented deficiencies in Zn levels (Table 4). Zn is an essential micronutrient for plants that plays a key role in photosynthetic redox reactions, and it is an essential cofactor for many enzymes involved in nitrogen metabolism and protein synthesis [39,40]. Zn solubility is strongly dependent on pH, and similar to Fe, Zn availability is low in calcareous soils with a pH > 7 and high bicarbonate content [40].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, blades collected in the 2018-19 season presented deficiencies in Zn levels (Table 4). Zn is an essential micronutrient for plants that plays a key role in photosynthetic redox reactions, and it is an essential cofactor for many enzymes involved in nitrogen metabolism and protein synthesis [39,40]. Zn solubility is strongly dependent on pH, and similar to Fe, Zn availability is low in calcareous soils with a pH > 7 and high bicarbonate content [40].…”
Section: Discussionmentioning
confidence: 99%
“…Zn is an essential micronutrient for plants that plays a key role in photosynthetic redox reactions, and it is an essential cofactor for many enzymes involved in nitrogen metabolism and protein synthesis [39,40]. Zn solubility is strongly dependent on pH, and similar to Fe, Zn availability is low in calcareous soils with a pH > 7 and high bicarbonate content [40]. Zn deficiency may alter the expression and function of proteins at metabolic level that results in different physiological symptoms characterized by root apex necrosis, and in a decline in starch production and sugar accumulation in leaves [40,41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies further indicated that the up-regulation of genes encoding C 2 H 2 , AP2, MYB, bHLH, and YABBY transcription factors in this study might have positively effects in the mechanism of Pb stress tolerance, through increasing the activity of CAT, POD, and SOD, enhancing the production of MDA and the sequestration of Pb. However, owing to some other transcription factors, including bZIP, SBP, and HB-other transcription factors were reported to involve in uptake and accumulation of trace elements, they might have negative effect on the regulation of Pb stress (Song et al, 2019).…”
Section: Discussionmentioning
confidence: 99%